Layer dependence of the photoelectrochemical performance of a WSe2 photocathode characterized using in situ microscale measurements. Issue 53 (30th September 2019) - Zhang, Yu; Xiao, Jingwei; Xie, Xi; Chen, Huanjun; Deng, Shaozhi
Abstract : The performance of WSe2 PEC cathode increased with decreasing number of layers. Monolayer WSe2 exhibited best PEC characteristics and IPCE efficiency. The basal-plane of WSe2 sheet had the same PEC catalytic activity with the edge sites. Abstract : Transition-metal dichalcogenide (TMD) materials are good candidates for photoelectrochemical (PEC) electrode materials because of their distinctive optoelectronic properties and catalytic activities. Monolayer WSe2 is a p-type semiconductor with a direct bandgap that makes it a suitable PEC cathode material. In the present work, in situ PEC characterization of a single sheet device was carried out at the microscale to explore its performance. The PEC characteristics were found to be strongly related to the number of WSe2 layers. Monolayer WSe2 exhibited a dominant large current density and incident photo-to-current efficiency (IPCE) compared with those of multilayer WSe2 . Its PEC performance decreased with increasing number of layers. The photocurrent mapping results also revealed that the basal-plane sites and the edge sites on a monolayer WSe2 sheet contributed equally to its catalytic activity, which is not consistent with traditional catalyst theory. The underlying mechanism is discussed.